2020
DOI: 10.3390/brainsci10121018
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Autism Research in the Field of Education in Web of Science: A Bibliometric Study

Abstract: Autism spectrum disorder (ASD) is conceived as a neurodevelopmental disorder. The scientific literature welcomes studies that reflect the possible singularities that people with ASD may present both in their daily lives and at an educational level. The main objective of this study is to analyze the scientific production on the term autism in Web of Science, focused on the educational field, in order to identify the research trends in this field of study. The intention is to offer researchers who study autism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…The research method chosen was based on a co-word analysis [39], as well as on the h, g, hg and q2 indices [40,41]. The analysis of co-words allows us to analyze the keywords reported from the different scientific documents, with the purpose of looking for connections between the topics studied on the state of the question, as well as predicting the issues that could potentially be considered in the near future [42].…”
Section: Methodsmentioning
confidence: 99%
“…The research method chosen was based on a co-word analysis [39], as well as on the h, g, hg and q2 indices [40,41]. The analysis of co-words allows us to analyze the keywords reported from the different scientific documents, with the purpose of looking for connections between the topics studied on the state of the question, as well as predicting the issues that could potentially be considered in the near future [42].…”
Section: Methodsmentioning
confidence: 99%
“…Some people think that many sources may indicate that the authors or documents have attracted the attention of researchers in specific fields [ 24 ]. In recent years, some studies have been conducted from the bibliometrics perspective: research on genetic factors in ASD [ 25 ], robot intervention research [ 26 ], education research [ 27 , 28 ], executive function research [ 29 ], virtual reality research [ 30 ], and a scientific research overview [ 31 ] were reviewed and analyzed. Specifically, Perez-Vazquez, E et al found, by analyzing the literature published between 2005 and 2017, that robots may help autistic children to experience real interactions in the future, but its methodological limitations will hinder the popularization of the research results in this field [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This work has been developed following the guidelines of experts in this study method (Carmona-Serrano et al, 2021;López-Belmonte et al, 2019;Rodríguez-García et al, 2019). Specifically, this research has been based on an analysis of co-words and various bibliometric indicators and indices (h, g, hg, q2) (López-Núñez et al, 2020;Soler-Costa et al, 2021). This will give rise to a set of maps with nodes that will establish the performance and location of subdomains of the constructs connected to DIPA.…”
Section: Methodsmentioning
confidence: 99%